Towards an Applicable True Cost-of-Living Index that Incorporates Housing - N. Anders Klevmarken (Uppsala University, Department of Economics, 2004)
A dynamic model of consumer behavior that incorporates the demand for housing is specified such that it is consistent with the general purpose of a consumer price index. From this model a true cost-of-living index that includes housing is derived. Being an ideal index it cannot be computed without imposing additional assumptions about the behavior of the consumer, but it is possible to draw conclusions about the prices and weights that should be used in conventional approximations to such an ideal index.
Keywords: C43; D91; 330; True cost-of-living index; compensation index; price index of housing; Verbraucherpreisindex; Wohnkosten; Indexberechnung